Corporate Social Responsibility (CSR): Mapping, Opportunities, Constrains, and Development Strategies in Bojonegoro Regency - Purnomo, Joko Hadi; Anam, Moh. Saiful (IDFoS Indonesia, 2021)
The purpose of this research was to identify and map Corporate Social Responsibility (CSR) and its forms in Bojonegoro Regency, identify the problems, opportunities and constraints in realizing CSR in Bojonegoro Regency, and formulate the most ideal CSR model development strategy in Bojonegoro Regency to be applied in the future. The research design used in this research was a combination of qualitative and quantitative approaches. The results of this research were CSR Implementation Patterns, including: Partnership, Community Empowerment, and Charity. The capacity of CSR activities includes amount of funds, number of Beneficiaries, and characteristics of beneficiaries. In 2014 the amount of CSR funds was Rp. 30,257,550,000. The number of individual beneficiaries was 2,730 people, while the CSR beneficiaries in the form of groups were 55 groups, while those in the form of organizations were 170 organizations. There were 112 villages that became CSR beneficiaries. The capability of implementing CSR included: the implementation of the CSR program has been in accordance with the program’s objectives when it was planned in accordance with the statement of 84% of companies. However, in the transparency sector, the CSR program had not been implemented optimally, it was approved by 76% of companies becoming the research respondents. The level of community participation in the CSR implementation was still low, as stated by 70% of companies. The sustainability of the CSR program had not run optimally marked by the level of program suitability that was still inappropriate. The synergy between companies and the government had not run smoothly, as research results only 68% of companies stated that it was appropriate.